Case report: Prolonged and severe hungry bone syndrome after parathyroidectomy in X-linked hypophosphatemia - Giulia Puliani; Valeria Hasenmajer; Matteo Spaziani; Matteo Spaziani; Federico Frusone; Chiara Tarantino; Francesco Angelini; Ludovica Vincenzi; Riccardo Lubrano; Alessia Marcellino; Marco Biffoni; Andrea M. Isidori; et al. (Frontiers in Endocrinology)
Tertiary hyperparathyroidism is characterized by hypercalcemia resulting from autonomous parathyroid hormone production and usually occurs after a prolonged period of secondary hyperparathyroidism. This condition can be a complication of X-linked hypophosphatemia (XLH), a rare genetic disease characterized by renal phosphate loss and consequent hypophosphatemia. Parathyroidectomy is considered the first-line therapy but surgical intervention can be complicated by hungry bone syndrome. A male Caucasian patient presented with XLH, diagnosed at the age of 3 years. At the age of 21, tertiary hyperparathyroidism occurred. Neck ultrasonography, neck magnetic resonance imaging, and 99Tc-sestamibi parathyroid scintigraphy revealed two hyperplastic parathyroid glands. To minimize the risk of hypercalcemia, calcimimetic therapy was initiated. After 6 months and preparation with 1,25-dihydroxy vitamin D, the patient underwent total parathyroidectomy with autotransplantation of half of a parathyroid gland into the sternocleidomastoid muscle. Histopathological examination revealed diffuse microscopical hyperplasia of the parathyroid glands. Despite oral supplementation with calcium carbonate and calcitriol, severe hypocalcemia developed on the second postoperative day, attributable to hungry bone syndrome. This finding was confirmed by an increase in bone turnover markers and a reduction in urinary calcium excretion. Hypocalcemia correction required continuous infusion of calcium gluconate for over 2 months. After approval, the patient began burosumab therapy with significant benefits. This case illustrates the complexity of treating tertiary hyperparathyroidism and mineral metabolism in patients with XLH. The hungry bone syndrome can complicate parathyroidectomy, exposing the patients to life-threatening risks. Burosumab therapy may reduce the risk of tertiary hyperparathyroidism developing in these patients.